Solitary dermal cylindroma: a rare case report - Wahyu Tri Widayati; . Irianiwati (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2019)
Dermal cylindromas are rare benign skin appendageal tumors that has two clinical presentation, solitary and multiple form. The diagnosis is unusual.However, it must be considered in clinical practice.A 51-year-old woman hadpainless nodule on right arm. Skin examinatipn revealedtwo fragmented nodules, 1x0.5x0.5cm, tan to white, and rubbery. Histopathological findings revealed a well demarcated and an unencapsulated epithelial dermal tumor, composed of numerous oval and polygonal nests molded into a